PENGARUH FRAUD DIAMOND DALAM MENDETEKSI FINANCIAL STATEMENT FRAUD - Prastyo, Adam Maulana; Sarwono, Aris Eddy; Puji Astuti, Dewi Saptantinah (Universitas Muhammadiyah Tangerang, 2022)
The purpose of this study is to determine the influence of diamond fraud elements consisting of pressure elements (which are proxied with financial stability, external pressure, and financial targets), oppoturnity elements (which are proxied by the nature of industry and ineffective monitoring), rationalization elements proxied by audit opinions, and capability elements proxied by changing directors to fraud fraud financial statements. This research uses a qualitative descriptive method with secondary data sources collected through literature studies. The results of this study show that the Fraud Diamond element can have an effect on detecting the occurrence of financial statement fraud. The higher the application of diamond fraud analysis, the less the risk of financial statement fraud fraud in the company. The application of diamond fraud analysis in internal control can anticipate fraud fraud in financial statements in the company. The better and higher the quality of diamond fraud analysis carried out in the company, the risk of fraud fraud in financial statements in the company can be minimized.